High-speed and high-resolution interrogation of FBG sensors using wavelength-to-time mapping and Gaussian filters - Fernández, Manuel Pablo (2019)
In this work we report a novel intensity-based technique for simultaneous high-speed and high-resolution interrogation of fiber Bragg grating (FBG) sensors. The method uses a couple of intensity Gaussian filters and the dispersion-induced wavelength-to-time mapping effect. The Bragg wavelength is retrieved by means of the amplitude comparison between the two filtered grating spectrums, which are mapped into a time-domain waveform. In this way, measurement distortions arising from residual power due to the grating sidelobes are completely avoided, and the wavelength measurement range is considerably extended with respect to the previously proposed schemes. We present the mathematical background for the interrogation of FBGs with an arbitrary bandwidth. In our proof-of-concept experiments, we achieved sensitivities of ∼20 pm with ultra-fast rates up to 264 MHz.